Relationship of downy mildew resistance with yield related traits helpful for achieving reliable selection criteria in opium poppy (Papaver somniferum L.) - Dubey, Mukesh; Dhawan, O.P. (The Indian Journal of Genetics and Plant Breeding, 2016)
Present study aims to understand the nature and degree of relationships between different morphometric and yield influencing traits using correlation and path coefficient analysis in medicinally important plant opium poppy. Genotypic and phenotypic correlation coefficients analysis showed significant negative correlation between downy mildew disease severity Index (DSI) and seed and straw yield. Furthermore, path analysis showed direct and positive effect of capsule diameter and number of capsule/plant to straw yield. In contrast, DSI had highest direct and negative contribution to straw yield. These results support effectiveness of selections for high seed and straw yield together with downey mildew-resistance in development of effective selection criteria for crop improvement.